Spectral response of gamma and electron irradiated pin photodiode - Onoda, S.; Hirao, T.; Laird, J.S.; Mori, H.; Okamoto, T.; Koizumi, Y.; Itoh, H. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
The optical spectral response of Si pin photodiodes was examined after gamma and electron irradiation. We observed both a significant decrease in the peak optical response and peak position with increasing total dose. This effect was successfully explained by modeling the degradation of the minority carrier diffusion length in the base region. The diffusion length damage factor was estimated in the context of the non-ionization energy loss (NIEL). A close agreement was found between the observed degradation behavior and that predicted by NIEL.